Bioacoustic Spectral Whistle Sound And Behaviour Of Male Dolphin Bottle Nose ( Tursiops aduncus) At Safari Park Indonesia, Cisarua Bogor - Muhamad Zainuddin Lubis; Sri Pujiyati; Totok Hestirianoto (Diponegoro University, 2016)
Whistle sound is generally used for echolocation purposes, while the sound of the blast-beat and whistles play a major role in internal and inter-group communication.The purpose of this research is to know the power spectral patterns and fluctuations in sound based on frequency and Power Spectral Density (PSD) of the sounds produced by dolphins and observing the position of dolphins , Noisy Time Domain (NTD) and behavior using underwater camera, and also comparing between time and sound spectrum. Data recording was taken at tha Safari Park of Cisarua Bogor in Indonesia, by taking data in show pool and show pool. The results showed that salinity before feeding time in the show pool with replication 1,2, and 3 has salinity value that is equal to 30 ‰. Data at the show pool before feeding with replications 1,2, and 3 has a salinity of 29 ‰. Power Spectral Density (PSD) of the whistle sound before feeding was different from one another, but it has the same frequency range. The highest intensity values is at sound whistle 3 before feeding time at the show pool with an intensity value of 28.03 dB with frequency interval of 14 642 Hz-16000 Hz. F-test at the show pool before meals has heterogeneous value. Treat before meals at the show pool has a value of P <0.001 and P <0.001. Value Noisy Time Domain have differences with each other and have a lot of different sound patterns. In general, there are real differences are evidenced by F test on a range of time at each whistle on physiotherapy and swimming pool show in the time before meals. The position of dolphins in a pool show more dominant and often in the bottom of the pool, the position of the dolphins affect the frequency.